Synthesis, characterization, X-ray structure and in vitro anti mycobacterial and antitumoral activities of Ru(II) phosphine/diimine complexes containing the "SpymMe(2)" ligand, SpymMe(2)=4,6-dimethyl-2-mercaptopyrimidine - do Nascimento, Fabio B.; Von Poelhsitz, Gustavo; Pavan, Fernando Rogério [UNESP]; Sato, Daisy N.; Leite, Clarice Queico Fujimura [UNESP]; Selistre-de-Araujo, Heloisa S.; Ellena, Javier; Castellano, Eduardo E.; Deflon, Victor M.; Batista, Alzir A. (Elsevier B.V., 2008)
The reaction of cis-[RuCl2(dppb)(N-N)], dppb = 1,4-bis(diphenylphosphino)butane, complexes with the ligand HSpymMe(2), 4,6-dimethyl-2-mercaptopyrimidine, yielded the cationic complexes [Ru(SpymMe(2))(dppb)(N-N)]PF6, N-N = bipy (1) and Me-bipy (2), bipy = 2,2'-bipyridine and Me-bipy = 4,4'dimethyl-2,2'-bipyridine, which were characterized by spectroscopic and electrochemical techniques and X-ray crystallography and elemental analysis. Additionally, preliminary in vitro tests for antimycobacterial activity against Mycobacterium tuberculosis H37Rv ATCC 27264 and antitumor activity against the MDA-MB-231 human breast tumor cell line were carried out on the new complexes and also on the precursors cis-[RuCl2(dppb)(N-N)], N-N = bipy (3) and Me-bipy (4) and the free ligands dppb, bipy, Me-bipy and SpymMe(2). The minimal inhibitory concentration (MIC) of compounds needed to kill 90% of mycobacterial cells and the IC50 values for the antitumor activity were determined. Compounds 1-4 exhibited good in vitro activity against M. tuberculosis, with MIC values ranging between 0.78 and 6.25 mu g/mL, compared to the free ligands (MIC of 25 to >50 mu g/mL) and the drugs used to treat tuberculosis. Complexes I and 2 also showed promising antitumor activity, with IC50 values of 0.46 +/- 0.02 and 0.43 +/- 0.08 mu M, respectively, against MDA-MB-231 breast tumor cells. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: ruthenium (II) complex; cytotoxicity; antimycobacterial activity; dppb; 4,6-dimethyl-2-mercaptopyrimidine